LGBT-Parent Families - Goldberg, Abbie E.; Allen, Katherine R. (Springer, 2013)
In 2003, I began teaching an undergraduate course titled “Sexual Diversity in Society” in what proved to be a turning point year for North American struggles for LGBT family rights. Gay rights plaintiffs in the USA and Canada scored a series of landmark court victories that year. State and provincial Supreme Courts in Massachusetts, Ontario, and British Columbia became the fi rst in this hemisphere to judge bans on same-sex marriage unconstitutional, and in its historic ruling in the Lawrence v. Texas case, the USA Supreme Court reversed itself by overturning antisodomy laws. A scathing dissent by Justice Scalia correctly forecast the implications of this decision for the ultimate legalization of same-sex marriage. I always begin my courses on sexual diversity by conducting an anonymous, informal survey about my students’ sexual experiences, beliefs, attitudes, identities, and aspirations. Over the course of the past decade, I’ve noticed two intriguing, super fi cially contradictory, trends in the data produced by this decidedly unrepresentative sampling method. Unexpectedly, the number of women who label themselves lesbian has declined sharply, and the ranks of students claiming gay, or even straight, identities have been ebbing as well. Instead, students with nonconforming sexual or gender inclinations and practices, and women especially, have become more apt to describe themselves as “questioning, curious, undecided, or queer.” Some refuse to de fi ne their sexuality at all.
Innovations in Research and Implications for Practice